1981
DOI: 10.1007/bf00237343
|View full text |Cite
|
Sign up to set email alerts
|

Magnification factor and receptive field size in foveal striate cortex of the monkey

Abstract: Receptive field size and magnification have been studied in striate cortex of awake, behaving rhesus monkeys at visual eccentricities in the range of 5-160 min. The major findings that emerge are (1) magnification in the foveola achieves values in the range of 30 mm/deg, (2) mean field size is not proportional to inverse magnification in contrast with previous reports, and (3) the product, magnification X aggregate field size, is greater in central vision than in peripheral vision. Thus, a point of light proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
292
4
3

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(328 citation statements)
references
References 21 publications
29
292
4
3
Order By: Relevance
“…This difference between Eh and E,, implies that at least two scaling factors are required to superimpose the peripheral data onto the fovea1 values. Our present values of E,, fall within the range of -0.8 to -0.4 deg obtained for positional acuities in our previous studies Yap et al, 1987;Levi & Klein, 1989) and are compatible with recent estimates of the macaque Vl cortical magnification factor (Dow et al, 1981;Tootell et al, 1982;and Van Essen et al, 1984). However, it is interesting to note that the E,, value of observer YLY for 2-dot separation discrimination is close to but slightly larger than that previously determined for 3-dot bisection for both the optimum threshold (-0.57 + 0.04) and the optimum separation (-0.61 + 0.07) (upper arrow, Fig.…”
Section: T(e S) = Tmi"(e) + Andis -Smin(e)ivsupporting
confidence: 93%
See 1 more Smart Citation
“…This difference between Eh and E,, implies that at least two scaling factors are required to superimpose the peripheral data onto the fovea1 values. Our present values of E,, fall within the range of -0.8 to -0.4 deg obtained for positional acuities in our previous studies Yap et al, 1987;Levi & Klein, 1989) and are compatible with recent estimates of the macaque Vl cortical magnification factor (Dow et al, 1981;Tootell et al, 1982;and Van Essen et al, 1984). However, it is interesting to note that the E,, value of observer YLY for 2-dot separation discrimination is close to but slightly larger than that previously determined for 3-dot bisection for both the optimum threshold (-0.57 + 0.04) and the optimum separation (-0.61 + 0.07) (upper arrow, Fig.…”
Section: T(e S) = Tmi"(e) + Andis -Smin(e)ivsupporting
confidence: 93%
“…For tasks which scale with eccentricity, there is often a striking resemblance between the rates of change of the behavioural thresholds and the morphology of either the retina or primary visual cortex. The variation of human resolution and contrast sensitivity within the central 10 deg parallels that of human and monkey cone spacing (Rolls & Cowey, 1970;Thibos, Cheney & Walsh, 1987;and Williams & Coletta, 1987), ganglion cell separationz (Weymouth, 1958;Rolls & Cowey, 1970;Drasdo, 1977;Rovamo, Virsu & Nasanen, 1978;Levi, Klein & Aitsebaomo, 1985;and Schein, 1987) receptive field size (Dow, Snyder & Bauer, 1981). The precision of bisecting the space between two features also scales to a single factor for a wide range of feature-separations , although its scaling factor is comparable to current estimates of the monkey Vl cortical magnification factor (Dow et al, 1981;Tootell, Silverman, Switkes & De Valois, 1982;and Van Essen, Newsome & Maunsell, 1984) which falls off three to four times faster than contrast sensitivity and resolution .…”
Section: Introductionmentioning
confidence: 83%
“…the eccentricity of the center of the blind spotabout 16.5 deg), E2 is the eccentricity in deg at which cortical magniftcation has dropped to 0.5*M, (the fovea1 magnification factor in ~/deg) and k = (Mr*EZ)-'. For the rhesus monkey the following parameters have been reported (Levi et al,, 1985;Dow, Snyder, Vautin & Bauer, 1981) Another study suggested a similar expression for the variation of linear cortical magnification with eccentricity (LeVay et al, 1985) based on results reported in earlier studies (Hubel & Wiesel, 1974;Hubel & Freeman, 1977). According to this study the expression for M for the macaque monkey is given by:…”
Section: (A) Estimating the Cortical Extent Of Contour Interactionmentioning
confidence: 69%
“…The specific functions tested were chosen to approximate the observed variation in the CMF across the visual field (Rovamo & Virsu, 1979). There are disagreements in the literature as to the specific function that relates CMF to eccentricity (Dow, Snyder, Vautin & Bauer, 1981;Levi et al, 1985;Rovamo & Raninen, 1984), but this issue is not addressed here. Rather, several candidate linear functions were chosen that differed in central blur (at 80 eccentricity), peripheral blur (at 400 eccentricity), and the blur gradient between 8' and 400 eccentricity.…”
Section: Experiments 1 Perceptual Assessment Of Wide-field Variable-mentioning
confidence: 99%